Characterization of interdiffusion mechanisms during co-bonding of unsaturated polyester resin to thermoplastics with different thermodynamic affinities. (17th November 2020) - Monfared Zanjani, Jamal Seyyed; Baran, Ismet; Akkerman, Remko
Abstract: Co-bonding of thermoplastics to thermosets remains as a challenge in hybrid composites manufacturing. The interphase of the joint is controlled by the thermodynamic affinity and the processing condition. Thus, the main objective of this study is to describe the interphase formation mechanisms between a thermoset resin and thermoplastics. Therefore, a methodology is developed to predict, control, and analyse the interphase morphology experimentally while modelling approaches are used to assess the microstructure. Hansen solubility parameters are used to select thermoplastics with different thermodynamic affinities to the unsaturated polyester resin as the thermoset. The resin uptake experiments are conducted to identify the kinetics of diffusion and empirical models are recognised to predict the swelling at various processing temperatures. Next, a coarse grain lattice model is established which couples the resin uptake and microscopic observation to extract information on the microstructure of interphase through predicting volume fraction of resin at the interphase. Graphical abstract: Image 1 Highlights: Interphase formation mechanisms between thermoset and thermoplastics are described. Hansen solubility parameters are used to select thermoplastics. Effective parameters are identified and used to control the interphase morphology. A Coarse grain lattice model is used to link diffusion kinetics to the microstructure.